(3GdUQGY GdJfXjej hGdCOGA GdhXjaj aj GdefXeGJ GdeYGUQIs - (3Sj MeOj(B, (3YHO GdeDefs; (3bQjbI, CSeGAs ((3GdLRGFQs (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjYs)
(3GdUQGY GdJfXjej, hGdCOGA GdhXjaj, eY CgejJg, heMOOGJg hhCfhGYg, hYdGbJg HGdCOGA GdhXjajeY BKGQg aj GdefXeI, hCSGdjH eYGdLJghOhQgG aj JaYjd GdCOGA GdhXjajaj GdefXeI hcPGdc GSJQGJjLjGJ GdUQGY GdJfXjejhGfYcGSGJgG Ydi GdCOGJA GdhXjajhOhQgG aj JaYjdg(B.s
Keywords: (3GdCOGA GdhXjajs; (3GdQbGHI GdGOGQjIs; (3GdUQGY GdJfXjejs